All Days 2014
DOI: 10.2118/168579-ms
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Results of Proppant Transport in Complex Fracture Systems

Abstract: With a global paradigm shift towards exploring shale reservoirs, the industry focus has moved towards optimizing hydraulic fracturing in these reservoir types. Low-viscosity slickwater fracture treatments are commonly used as a completion technique in these ultra-low permeability reservoirs. Each shale reservoir is different due to the presence of in situ natural fractures and other geologic complexities, and thus the resultant hydraulic fracture network is distinct and the proppant transport in these "created… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
46
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 109 publications
(55 citation statements)
references
References 3 publications
8
46
0
1
Order By: Relevance
“…Several other authors have presented slot experiments, including Patankar et al (2002), Brannon et al (2006), Woodworth and Miskimins (2007), and Sahai et al (2014). Most of this work has been directed at determining equilibrium bank heights and critical fluid velocities.…”
Section: Large-scale Slot Tests: Previous Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Several other authors have presented slot experiments, including Patankar et al (2002), Brannon et al (2006), Woodworth and Miskimins (2007), and Sahai et al (2014). Most of this work has been directed at determining equilibrium bank heights and critical fluid velocities.…”
Section: Large-scale Slot Tests: Previous Workmentioning
confidence: 99%
“…Three different Advanced Ceramic Proppants (30/40, 40/50 and 50/60) were pumped though the slot described by Sahai et al (2014). Although the slot configuration included secondary slots, the main purpose of the work was to measure transport in the primary slot.…”
Section: Large-scale Slot Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sahai et al fabricated lab-scale experimental apparatus to evaluate proppant flow in secondary fractures and concluded that proppant was able to flow in secondary fractures by drag force of the fluid or rolling into them as a result of the effect of gravity. 11 Alotaibi et al extended this work and highlighted the mechanism of proppant transport during proppant bed development; they further included friction loss and proposed a scalable correlation for 30/70 brown sands to estimate the equilibrium sand bed height for different flow rates and sand concentrations. 12 Tong and Mohanty studied the proppant transport in fractures with different types of bypass angle, considering the effects of shear rate and proppant size.…”
Section: Introductionmentioning
confidence: 97%
“…Sahai et al . fabricated lab‐scale experimental apparatus to evaluate proppant flow in secondary fractures and concluded that proppant was able to flow in secondary fractures by drag force of the fluid or rolling into them as a result of the effect of gravity . Alotaibi et al .…”
Section: Introductionmentioning
confidence: 99%